Repositioning Lidocaine as an Anticancer Drug: The Role Beyond Anesthesia - Zhou, Daipeng; Wang, Lei; Cui, Qingbin; Iftikhar, Ryma; Xia, Yanfei; Xu, Peng (Frontiers in Cell and Developmental Biology, 2020)
While cancer treatment has improved dramatically, it has also encountered many critical challenges, such as diseases recurrence, metastasis and drug resistance, making new drugs of novel mechanisms the urgent clinical need. The term drug repositioning, also known as old drugs for new uses, has emerged as one practical strategy to develop new anticancer drugs. Anesthetics have been widely used in surgical procedures to reduce the excruciating pain. Lidocaine, one of the most used local anesthetics in clinical settings, has been found to show multi-activities, including its potential in cancer treatment. Growing evidence shows that lidocaine may not only work as a chemosensitizer that sensitizes other conventional chemotherapeutics to certain resistant cancer cells, but also could suppress cancer cells growth by single use at different doses or concentrations. Lidocaine could suppress cancer cell growth in vitro and in vivo via multiple mechanisms, such as regulating epigenetic changes, promoting pro-apoptosis pathways, as well as regulating ABC transporters, metastasis and angiogenesis, etc., providing valuable information for its further application in cancer treatment and for new drug discovery. In addition, lidocaine is now under clinical trials to treat certain types of cancer. In the current review, we summarize the research and analyze the underlying mechanisms, and address key issues in this area.